Total Synthesis of an Exceptional Brominated 4‐Pyrone Derivative of Algal Origin: An Exercise in Gold Catalysis and Alkyne Metathesis. Issue 12 (25th February 2015) - Hoffmeister, Laura; Fukuda, Tsutomu; Pototschnig, Gerit; Fürstner, Alois
Abstract A concise approach to the algal metabolite 1 is described, which also determines the previously unknown stereostructure of this natural product. Compound 1 is distinguished by a rare brominated 4‐pyrone nucleus linked as a ketene–acetal to a polyunsaturated macrocyclic scaffold comprising an extra homoallylic bromide entity. The synthesis of 1 is based on the elaboration and selective functionalization of the linear precursor 23 endowed with no less than six different sites of unsaturation including the highly enolized oxo‐alkanoate function. Key to success was the formation of the 2‐alkoxy‐4‐pyrone ring by a novel gold‐catalyzed transformation which engages only the acetylenic β‐ketoester substructure of 23 but leaves all other π‐bonds untouched. The synthesis was completed by a ring‐closing alkyne metathesis to forge the signature cycloalkyne motif of 1 followed by selective bromination of the ketene–acetal site in the resulting product 27 without touching the skipped diene–yne substructure resident within the macrocyclic tether.